PERAN KEPERCAYAAN DALAM MEMEDIASI HUBUNGAN ANTARA PERSEPSI NILAI DAN KEPUTUSAN PEMBELIAN PRODUK HIJAU HERBALIFE DI KOTA DENPASAR - Pemayun, Cok Istri Shintia Dewi Haruna; Suasana, I Gst Agung Ketut Gede (E-Jurnal Manajemen; Vol 4 No 12 (2015), 2015)
This study aims to determine the effect of perceived value and purchasing decisions through confidence in Herbalife green products related to do with environmental issues. Data collection techniques in the form of a questionnaire which contains a declaration of the 16 indicators. Total sample size of 120 respondents was determined by using purposive sampling method. Data analysis method used was a path analysis (path analysis) accompanied Sobel Test is used to test the hypothesis formulated. Results of this research indicate that the perception of the value of positive and significant impact on purchasing decisions Herbalife green products in Denpasar. Perception of the value of positive and significant impact on the trust green products Herbalife in Denpasar. Confidence positive and significant impact on purchasing decisions Herbalife green products in Denpasar. The role of trust is positively and significantly mediates the relationship between the perception of the value of the green product purchasing decisions Herbalife in Denpasar
Keywords: persepsi nilai, kepercayaan, keputusan pembelian